A mixed studies systematic review and meta-analysis of school–based interventions to promote physical activity and/or reduce sedentary time in children - Kelly Mackintosh (Journal of Sport and Health Science, 2019)
PurposeThe aim of this mixed-studies systematic review was to ascertain the effectiveness of school-based interventions at increasing physical activity (PA) and/or reducing sedentary time (ST) in children aged 5 to 11 years, as well as to explore effectiveness in relation to categories of the theory of expanded, extended and enhanced opportunity (TEO).MethodsAdhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, 5 databases were searched using pre-defined search terms. Following title and abstract screening of 1115 records, the removal of duplicates (n = 584) and articles that did not meet the inclusion criteria agreed to a priori (n = 419) resulted in 112 records that were full-text screened. Two independent reviewers subsequently used the mixed-methods appraisal tool to assess the methodological quality of 57 full-text studies that met the inclusion criteria after full-text screening. The interventions were summarised using the TIDierR checklist and TEO. The strength of evidence was determined using a five-level rating system utilising a published decision tree.ResultsOverall evidence ratings for interventions implemented within school settings were no evidence on moderate-to-vigorous physical activity and inconclusive evidence on sedentary time. In relation to the TEO, expansion of PA appeared to be the most promising intervention type for MVPA, with moderate evidence of effect, whereas extension and enhancement of PA opportunity demonstrated no evidence of effect. A critical issue of possible compensatory behavior was identified by analysis of intervention effect in relation to PA measurement duration; when studies measured changes in PA during the actual intervention there was moderate evidence of effect, whereas those that measured changes in PA during the school day presented inconclusive evidence of effect and those that measured changes in PA over a whole day yielded no evidence of effect. Two meta-analysis of those studies using a whole-day accelerometer measure for MVPA or ST showed a significant but moderate effect for MVPA (effect size (ES) = 0.51; 95% Confidence Interval (CI): 0.02–0.99) and a large but non-significant effect for ST 1.15 (95%CI: –1.03 to 3.33); both meta-analysis demonstrated low precision, considerable inconsistency, and high heterogeneity.ConclusionThe findings have important implications for future intervention research in terms of intervention design, implementation, and evaluation.